Will the MEGA2 edition be a watershed in interpreting Marx?. Issue 5 (3rd September 2018) - Kurz, Heinz D.
Abstract: The MEGA 2 edition is a watershed in interpreting important aspects of Marx's oeuvre, but not all of them. It provides hints as to why Marx failed to complete his magnum opus, Capital, and informs about his doubts regarding the "law of motion" of capitalism centred on the "law of the falling tendency of the rate of profit" he was keen to establish.